Interpersonal Physiological Synchrony for Detecting Moments of Connection in Persons With Dementia: A Pilot Study - Fu, Dannie; Incio-Serra, Natalia; Motta-Ochoa, Rossio; Blain-Moraes, Stefanie (Frontiers in Psychology, 2021)
Interpersonal physiological synchrony has been successfully used to characterize social interactions and social processes during a variety of interpersonal interactions. To date, there are a handful of measures of interpersonal physiological synchrony, but those that exist have only been validated on able-bodied adults. Here, we present a novel information-theory based measure of interpersonal physiological synchrony – normalized Symbolic Transfer Entropy (NSTE) – and compare its performance with a popular physiological synchrony measure – physiological concordance and single session index (SSI). Using wearable sensors, we measured the electrodermal activity (EDA) of five individuals with dementia and six able-bodied individuals as they participated in a movement activity that aimed to foster connection in persons with dementia. We calculated time-resolved NSTE and SSI measures for case studies of three dyads and compared them against moments of observed interpersonal connection in video recordings of the activity. Our findings suggest that NSTE-based measures of interpersonal physiological synchrony may be able to provide additional advantages on top of SSI, including resolving moments of ambiguous SSI and providing information about the direction of information flow between participants. This study also investigated the feasibility of using interpersonal synchrony to gain insight into moments of connection experienced by individuals with dementia and further encourages exploration of these measures in other populations with reduced communicative abilities.